2019
DOI: 10.1001/jamaoncol.2019.1838
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Molecular Relapse Detection in Early-Stage Breast Cancer

Abstract: IMPORTANCE Current treatment cures most cases of early-stage, primary breast cancer. However, better techniques are required to identify which patients are at risk of relapse.OBJECTIVE To assess the clinical validity of molecular relapse detection with circulating tumor DNA (ctDNA) analysis in early-stage breast cancer. DESIGN, SETTING, AND PARTICIPANTSThis prospective, multicenter, sample collection, validation study conducted at 5 United Kingdom medical centers from November 24, 2011, to October 18, 2016, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
261
1
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(284 citation statements)
references
References 15 publications
15
261
1
7
Order By: Relevance
“…14). Garcia-Murillas and colleagues (2019) did not compute clinical sensitivity at postoperative but stated that most patients who experienced recurrence did not have an initial MRDþ test at postoperative (15). Meanwhile, Coombes and colleagues reported higher sensitivity in the first postoperative sample tested per patient but this was later for most patients, up to 3 years after completion of adjuvant chemotherapy (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14). Garcia-Murillas and colleagues (2019) did not compute clinical sensitivity at postoperative but stated that most patients who experienced recurrence did not have an initial MRDþ test at postoperative (15). Meanwhile, Coombes and colleagues reported higher sensitivity in the first postoperative sample tested per patient but this was later for most patients, up to 3 years after completion of adjuvant chemotherapy (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that liquid biopsies can detect minimal residual disease (MRD) in multiple cancer types (8)(9)(10)(11)(12) including breast (13)(14)(15), by tracking tumor mutations in circulating cell-free DNA (cfDNA). However, in these previous studies, clinical sensitivity has been limited at the early postoperative time points, at which treatment decisions are typically made, and the lead time prior to clinical presentation of overt metastatic disease has been relatively short.…”
Section: Introductionmentioning
confidence: 99%
“…As with CTCs, numerous methods are available for total cfDNA extraction from both serum and plasma, with studies illustrating that several pre-analytical factors affect yield and downstream analysis post-venepuncture, including the blood tube used, number of centrifugation steps, centrifugal speed, cfDNA extraction method, and ctDNA detection methods [19][20][21]. Methods employed for detection of ctDNA depend upon the question being asked, with whole genome/exome next generation sequencing (NGS) being performed to obtain a global view of genomic changes associated with disease progression [22,23] (however, this is hampered by low sensitivity), targeted sequencing to obtain higher sensitivity (1 ctDNA molecule in 1000 cfDNA molecules) in a smaller number of genes [6,15,17,24,25], or digital droplet PCR (ddPCR) (usually analysis of one or two mutations to a sensitivity of one in 100,000) to detect early stage disease [14,26]. To date, only a handful of ctDNA tests have been approved by the U.S Food and Drug Administration (FDA) for use in metastatic and locally advanced NSCLC, and HR+, HER2-negative, advanced breast cancer in progression on or after endocrine therapy.…”
Section: Introductionmentioning
confidence: 99%
“…According to smaller trials the circulating DNA may also contribute to risk stratification in the follow-up of asymptomatic patients 43 , 44 , 45 , 46 . In a group of 101 women Garcia-Murillas et al were able to establish that serial ctDNA measurements can predict the risk of recurrence 44 . Blood tests were repeated every 3 months in the first year and then every 6 months for 5 years.…”
Section: Clinical Applications Of Liquid Biopsy In Early Breast Cancementioning
confidence: 99%
“…Kleineren Studien zufolge kann auch die zirkulierende DNA zur Risikostratifizierung der asymptomatischen Patientin während der Nachsorge beitragen 43 , 44 , 45 , 46 . So konnten Garcia-Murillas et al an einem Kollektiv von 101 Frauen zeigen, dass serielle Messungen der ctDNA das Rezidivrisiko voraussagen können 44 . Blutentnahmen erfolgten im 1.…”
Section: Potenzial Der Liquid Biopsy In Der Nachsorgeunclassified